2020
DOI: 10.1002/joc.6562
|View full text |Cite
|
Sign up to set email alerts
|

Topoclimatic zones and characteristics of the upper Ganga basin, Uttarakhand, India

Abstract: The upper Ganga basin (UGB) constituting Bhagirathi and Alakananda basins has been considered as a single hydrological unit so far with comparable climate forcing. Here, we show three distinct “topoclimatic zones” of this basin having characteristically different temperature, precipitation, and orographic processes. The orographic discontinuity forced by a mountain ridge with an average elevation of 5,200 m a.s.l. is instrumental in the development of these topoclimatic zones. The northern region of the basin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 74 publications
(106 reference statements)
0
9
0
Order By: Relevance
“…Small glaciers are more susceptible to climate fluctuations and respond faster to the changes. This has been illustrated by recent studies in the region, which suggested small glaciers are losing more mass than big glaciers in recent times (Bhambri et al 2012;Mir et al 2017;Yadav et al 2020). This event highlighted the need for improved monitoring of Himalayan cryospheric systems as complex interlinking snow, glacier, permafrost, geology, and climate cause such catastrophic events.…”
Section: Role Of Recent Changes In the Regional Climatementioning
confidence: 96%
See 3 more Smart Citations
“…Small glaciers are more susceptible to climate fluctuations and respond faster to the changes. This has been illustrated by recent studies in the region, which suggested small glaciers are losing more mass than big glaciers in recent times (Bhambri et al 2012;Mir et al 2017;Yadav et al 2020). This event highlighted the need for improved monitoring of Himalayan cryospheric systems as complex interlinking snow, glacier, permafrost, geology, and climate cause such catastrophic events.…”
Section: Role Of Recent Changes In the Regional Climatementioning
confidence: 96%
“…This is a critical factor as monsoon-dominated areas of Uttarakhand Himalaya have less than 20% glaciers compared to the monsoon deficit zone in the north of the TC, suggesting less favourable conditions of southern slopes for glaciers. This also demonstrated by shallower temperature lapse rates at the monsoon-dominated glacier areas suggesting a high energy system through latent heat release of precipitating monsoon (Thayyen et al 2005;Thayyen and Dimri 2018;Yadav et al 2020). Nearest high elevation precipitation station located at Chamoli (2640 m a.s.l.)…”
Section: Precipitation Over Hanging Glacier Catchment and Raunthigadmentioning
confidence: 99%
See 2 more Smart Citations
“…Where volume, V in km 3 and area, A in km 2 has been generated and built a continuous data series by incorporating the less accurate data in a hierarchical way (Yadav et al, 2020) . The remaining gap is filled by interpolation.…”
Section: Glacier Volume Estimationmentioning
confidence: 99%